THE ESSENCE OF THE FORMATION OF ENVIRONMENTAL CULTURE OF ELEMENTARY SCHOOL STUDENTS (World Bulletin of Management and Law, 2023)
This article is devoted to the formation of the ecological culture of primary school students, love of nature and its rational use.
Keywords: Nature; ecology; ecological culture; environmental awareness